COMPARATIVE STUDY BETWEEN GIVING CIPROFLOXACIN SINGLE DOSE WITH DIVIDED DOSES CIPROFLOXACIN ON THE TREATMENT GONORRHOEA EMERGENCE OF RESISTANCE - Widodo, F. Y. (Universitas Wijaya Kusuma Surabaya, 2010)
Recently encountered the resistance to the use of single-dose ciprofloxacin as therapy gonorrhea, so it mustconsider the use of other drugs as an alternative. This study aims to find out the effectiveness of the drug ciprofloxacindivided doses (2 X 500 mg. for five days) to prevent gonorrhea disease resistance. From the results of this study can beseen, that the administration of Ciprofloxacin therapy divided doses (2 X 500 mg per day up to 5 days) for patientsurethriris gonorhoea, it shows significantly better results when compared with single dose of 1500 mg.